Virtual training system for robotics applications in industrial processes. - Cobo Freire, Erick Bryan (2022)
This work presents the development of a virtual reality training sys tem applied to industrial robotics and oriented to the teaching learning processes. The system considers a manipulator anthropomorphic industrial robot of 6DOF to perform autonomous object manipulation tasks in two virtual environments. The virtual environments are developed in the graphic engine Unity3D, the envi ronment exchanges information with MATLAB by shared memory to execute position and trajectory control algorithms for the operating end of the manip ulator robot. The virtual training system connects whit an Android mobile app that considers the following control panel functions: articular coordinate system, velocity configuration and dead man switch. Finally, evaluations of the developed virtual environments, the mobile application and the control algorithm are carried out to guarantee the usability of the virtual training system in the teaching-learning processes.